Preparation of Pt-Catalyst by Poly(p-phenylenediamine) Nanocomposites Assisted by Microwave Radiation for Proton Exchange Membrane Fuel Cell - Wang, Yen-Zen (Polymers (Basel), 2018)
The Pt elements are prepared via the redox reaction with microwave (MW) irradiation in the presence of poly(p-phenylenediamine) (PpPD) which is polymerized on XC72 carbon matrix (PpPD/XC72), behaving as reducing agent. The free primary amines of PpPD are actually converted (oxidized) to secondary ones (5,10-dihydrophenazine) after MW irradiation. Transmission electronic microscopy (TEM) micrographs reveal the prepared Pt nanoparticles are well-dispersed on the carbon matrix like commercial Pt-implanted carbon nanocomposite (Pt/C). From the residue weights of thermogravimetric analysis (TGA) thermograms of Pt-loaded PpPD/XC72 (PpPD/XC72-Pt-MW), more Pt (18.49 wt %) nanoparticles are implanted on PpPD/XC72 composite. The Pt-implanted wt % on PpPD/XC72 matrix is just slightly lower than that of commercial Pt/C (22.30 wt %). The Pt-catalyst supports of PpPD/XC72-Pt-MW illustrate typical cyclic voltammograms (C-V) of Pt-catalyst, including significant Pt–H oxidation and Pt–O reduction peaks. The electrochemical active surface area of PpPD/XC72-Pt-MW is found to be as high as 60.1 m(2) g(−1). Max. number of electron transfer during oxygen reduction reaction (ORR) approaches 3.83 for PpPD/XC72-Pt-MW, higher than that of commercial Pt/C (3.62). Single cell based on PpPD/XC72-Pt-MW demonstrates much higher specific max. power density to be 34.6 mW cm(−2) Pt, higher than that single cell prepared with commercial Pt/C electrode (30.6 mW cm(−2) Pt).